Nonlinear backstepping control for PMSG wind turbine used on the real wind profile of the Dakhla‐Morocco city. (7th February 2020) - El Mourabit, Youness; Derouich, Aziz; El Ghzizal, Abdelaziz; El Ouanjli, Najib; Zamzoum, Othmane
Summary: This paper deals with a nonlinear control of a wind energy conversion system (WECS) based on a permanent magnet synchronous generator (PMSG) interconnected to the distribution grid. The system connected to the grid is achieved by two IGBT based back‐to‐back converters controlled by pulse width modulation (PWM) and a capacitor as a DC link between them. Firstly, a literature review on the recent studies of nonlinear control in the wind energy field is introduced. Subsequently, a complete description of the wind energy conversion system with its dynamic modeling is presented. The second part of this article focused on the proposed control laws that rely on backstepping control as well as the maximum power point tracking (MPPT) command. The main objective of the control is to optimize the extraction of the wind power in the presence of a real wind profile and to keep the PMSG working properly with the best performance in both static and dynamic modes. The wind profile of this simulation is measured from the Dakhla region in Morocco to test the system robustness against real conditions. The simulation analysis prove the validation of the control strategy using a 2‐MW wind turbine and showed that the backstepping control based on the Lyapunov stability technique offers excellent results in terms of THD rate that does not exceed 0.95%.